Students with specific learning disabilities in the higher education system in Israel: successes and challenges - Mandelblit, Ronit (Rocznik Pedagogiczny, 2019)
Studies show the very high probability that a child with learning disabilities will grow up to be an adult with learning disabilities and will experience difficulties in his academic or professional stud- ies and in the world of employment. Today, there is an increase in the number of students with learn- ing disabilities in academic institutions in Israel and around the world, with the extent of students with learning disabilities in Israel being estimated at up to 15% of diagnosed students. The article discusses the problem that most studies address children and teens with learning disabilities, while knowledge about coping with students with learning disabilities in the higher education system is limited. Moreover, there seems to be no uniform policy on supporting these students. The article is addressed to policymakers and lawmakers in Israel’s higher education system, with the aim of presenting current support and proposing changes and improvements intended for these students.